Outcomes of a “virtual think tank” to establish collaborative leadership initiative plans (“CLIPs”) - Whitney D. Maxwell; Kerry K. Fierke; Gregory M. Zumach (Exploratory Research in Clinical and Social Pharmacy, 2024)
Goal: The American Association of Colleges of Pharmacy (AACP) Leadership Development Special Interest Group (LD SIG) held a one-hour “Virtual Think Tank” (VTT) interactive session in 2020 for pharmacy educators interested in leadership development. The purpose of this study was to evaluate the quantitative and qualitative outcomes of this VTT. Methods: VTT attendees worked together in small groups created based on pre-selected common interest areas related to leadership development to create collaborative leadership initiative plans (CLIPs), which were ideas for new collaborative scholarly or programmatic initiatives. Principal findings: Quantitative outcomes of this VTT included statistically significant increases in positive perceptions toward the organization hosting the VTT regarding networking, scholarly collaboration, educational collaboration, and professional service opportunities, as well as significant improvements in attitudes regarding engagement with the sponsoring organization. Additionally, 18.4% of VTT attendees continued communicating with CLIP groups post-VTT and 13.2% of respondents indicated that they successfully implemented the CLIP ideas that were generated during the VTT. Qualitative outcomes included findings that the two most commonly encountered barriers were insufficient traction of the initial idea and lack of time (41.9% (n = 13) for both). Other barriers included lack of alignment with priorities at 12.9% (n = 4). Practical applications: This leadership VTT for pharmacy academicians led to development and implementation of important scholarly and programmatic outcomes, and fostered cross-institutional partnerships. Findings from this study evaluating a VTT provide a framework of expectations for other organizations seeking to implement a similar initiative.